Correlating Demographics and Well-being among Rural College Students in the Philippines - Resti Tito Villarino; Maureen Lorence Villarino; Maria Concepcion Temblor; Prosper Bernard; Michel Plaisent (Nurse Media: Journal of Nursing, 2023)
Background: College students’ well-being is influenced by various factors such as age, gender, and socio-economic levels, but research findings on their correlation are inconsistent.